Unraveling Heterogeneity in the Aging Hematopoietic Stem Cell Compartment: An Insight From Single-cell Approaches - Fei Yang; Craig Nourse; G. Vignir Helgason; Kristina Kirschner (HemaSphere, 2023)
Specific cell types and, therefore, organs respond differently during aging. This is also true for the hematopoietic system, where it has been demonstrated that hematopoietic stem cells alter a variety of features, such as their metabolism, and accumulate DNA damage, which can lead to clonal outgrowth over time. In addition, profound changes in the bone marrow microenvironment upon aging lead to senescence in certain cell types such as mesenchymal stem cells and result in increased inflammation. This heterogeneity makes it difficult to pinpoint the molecular drivers of organismal aging gained from bulk approaches, such as RNA sequencing. A better understanding of the heterogeneity underlying the aging process in the hematopoietic compartment is, therefore, needed. With the advances of single-cell technologies in recent years, it is now possible to address fundamental questions of aging. In this review, we discuss how single-cell approaches can and indeed are already being used to understand changes observed during aging in the hematopoietic compartment. We will touch on established and novel methods for flow cytometric detection, single-cell culture approaches, and single-cell omics.